VISITOR INTEREST AT THE ASAHAN REGENCY LIBRARY AND ARCHIVES DEPARTMENT (International Journal of Cultural and Social Science, 2026)
This study aims to identify the factors influencing visitors’ interest in visiting the Regional Library and Archives Office of Asahan Regency. The research employed a quantitative approach with a sample of 112 respondents selected using accidental sampling. Data were collected through questionnaires and analyzed using Exploratory Factor Analysis (EFA) with SPSS version 27. The results indicate that the data are feasible for factor analysis, as shown by the KMO value of 0.807 and a significance level of 0.000. The analysis produced three main factors with eigenvalues greater than 1, namely 4.728, 2.444, and 1.214. The first factor relates to service quality and library facilities, the second factor represents internal user conditions, and the third factor reflects social influences. Among all variables, internet dependency shows the highest contribution, while location access shows the lowest. These findings provide empirical evidence that visitors’ interest is influenced by service quality, personal motivation, and social environment.